Study of the Failure Mode of a Jointed Rock Mass due to a Stress Wave - Xi Kun Qian; Cong Cong Li (Advances in Civil Engineering)
The mechanical response and failure process of a jointed rock mass subjected to dynamic loading is very important for the safety and stability of rock engineering projects. In this study, we use RFPA2D-Dynamic, a rock dynamic failure process analysis platform, to establish a two-dimensional impact model of a jointed rock mass to analyze the mechanism of crack propagation in a jointed rock mass with preexisting cracks under dynamic loading. We discuss the influence of the stress wavelength and precrack inclination on the dynamic failure process and mode of the rock mass and compare this failure process with the failure model under static loading. The results show that the dynamic failure process and crack initiation type of a jointed rock mass are closely related to the stress wavelength. For a given peak, as the stress wavelength increases, the failure mode changes from local cracking that occurs above the precracks to a global instability caused by wing cracks. Meanwhile, as the wavelength increases, the shear cracks and mixed tensile-shear cracks generated at the two ends of the precracks are replaced by tensile cracks. The precrack inclination on a jointed rock mass mainly affects the strength of the jointed rock mass and the final failure mode. Specifically, when the joint inclination is small, the rock mass is severely damaged in the region above the precracks because the stress wave forms a region of cracks with a concentrated distribution. As the joint inclination increases, the damaged region becomes larger while the rock mass is less prone to failure; the strength of the rock mass gradually increases, and the wing cracks produced at the two ends of precracks propagate toward the upper and lower ends of the rock mass. However, when the stress wavelength is small, the precracks of different inclinations form cracks in the region above the precracks with a length similar to the precracks. For this condition, the propagation of the cracks is mainly controlled by the stress wavelength, while the influence of the inclination of the precracks is not significant. There is a significant difference between the failure modes of a rock specimen under dynamic loading or static loading because the stress wave produces a reflected tension wave in the direction parallel to the wave attack of the joint plane, which leads to spalling, while the wing cracks are more likely to occur under static loading.